Serum insulin-like growth factor-1 as a potential prognostic biomarker for heart failure with reduced ejection fraction: a meta-analysis - Liu, Tingting; Li, Fangyu; Fei, Yihuan; Sun, Fangling; Chen, Mengqi; Tian, Xin; Zheng, Wenrong; Zhu, Zixin; Wang, Wen (Frontiers in Cardiovascular Medicine, 2024)
Background Most studies have indicated that peripheral insulin-like growth levels factor-1 (IGF-1) is valuable in diagnosing heart failure, although the results have been inconsistent. To help solve the debate, we performed a meta-analysis to explore the relationship between IGF-1 and heart failure (HF). Methods We conducted an extensive search across various databases such as Embase, Cochrane Library, Pubmed, Medline, and Web of Science on May 30, 2023. From the extensive pool of studies, we selected 16 relevant articles, encompassing a total of 1,380 cases and 1,153 controls, to conduct a rigorous meta-analysis. Results The total results indicated that there is an association between lower IGF-1 level and HF. The random-effects model yielded a pooled standardized mean difference (SMD) of −0.598 (95% CI: −1.081 to −0.116, P = 0.015). Further subgroup analysis also showed that IGF-1 levels were associated with HF in the age difference ≥5 years subgroup and body mass index difference >1 subgroup. Additionally, significant association between IGF-1 levels and HF were detected in the “serum” samples and “Europe” subgroups. Importantly, we observed IGF-1 showed significant lower levels in patients with reduced ejection fraction (HFrEF) compared to the controls, not in patients with preserved ejection fraction (HFpEF). The Begg’s and Egger’s tests revealed no indication of publication bias. Conclusions Our meta-analysis has provided evidence suggesting a substantial correlation between reduced levels of IGF-1 and the occurrence of HF. Further prospective studies are necessary to ascertain the use of IGF-1 as a reliable biomarker for diagnosing HF, especially for HFrEF. But the diagnosis of HFpEF should be cautious.